Caribbean Community : crossroads to the future. - JAGAN, Cheddi (1994)
Notes that the economic progress of CARICOM has been disappointing, for example, the widening trade gap between the region's MDCs and LDCs, few regional industries. Questions whether CARICOM is an anachroism in the modern trend to wide-market groupings such as NAFTA.